Population‐based 10‐year oncologic outcomes after low‐dose‐rate brachytherapy for low‐risk and intermediate‐risk prostate cancer1. Issue 8 (26th December 2012) - Morris, W. James; Keyes, Mira; Spadinger, Ingrid; Kwan, Winkle; Liu, Mitchell; McKenzie, Michael; Pai, Howard; Pickles, Tom; Tyldesley, Scott
Abstract: BACKGROUND: The objective of this study was to report the rates of disease‐free survival (DFS), cause‐specific survival (CSS), and overall survival after low‐dose‐rate (LDR) prostate brachytherapy (PB). METHODS: Data from 1006 consecutive patients with prostate cancer who received LDR‐PB and underwent implantation on or before October 23, 2003 were extracted from a prospective database on November 11, 2011. The selected patients had low‐risk (58%) or intermediate‐risk (42%) disease according to National Comprehensive Cancer Network criteria. The Phoenix threshold was used to define biochemical relapse. Sixty‐five percent of patients received 3 months of neoadjuvant androgen‐deprivation therapy (ADT) and 3 months of concomitant ADT. Univariate and multivariate analyses are reported in relation to patient, tumor, and treatment variables. RESULTS: The median follow‐up was 7.5 years. By using Fine and Gray competing risks analysis, the 5‐year and 10‐year actuarial DFS rates were 96.7% (95% confidence interval, 95.2%‐97.7%) and 94.1% (95% confidence interval, 92%‐95.6%), respectively. When applied to the whole cohort, none of the usual prognostic variables, including dose metrics, were correlated with DFS. However, in both univariate and multivariate models, increasing dose was the only covariate that correlated with improved DFS for the subset of men (N = 348) who did not receive ADT ( P = .043). The actuarial 10‐year CSS rate was 99.1% (95% confidence interval, 97.3%‐99.7%). The overall survival rate was 93.8% at 5 years (95% confidence interval, 92%‐95.1%) and 83.5% at 10 years (95% confidence interval, 79.8%‐86.6%). Only age at implantation ( P = .0001) was correlated with overall survival in multivariate analysis. CONCLUSIONS: In a consecutive cohort of 1006 men with National Comprehensive Cancer Network low‐risk and intermediate‐risk prostate cancer, the actuarial rate of recurrent disease after LDR‐PB was approximately 3% at 5 years and 6% at 10 years. Cancer 2013. © 2012 American Cancer Society. Abstract : In a population‐based cohort of 1006 patients with low‐risk and intermediate‐risk prostate cancer, the actuarial disease‐free survival (DFS) rates using competing risks (Fine and Gray) analysis after low‐dose‐rate brachytherapy are 96.7% at 5 years and 94.1% at 10 years using the standard Phoenix definition for biochemical recurrence. None of the traditional prognostic factors reaches statistical significance for DFS in univariate or multivariate analysis; however, among men who do not receive neoadjuvant and concomitant androgen‐deprivation therapy (N = 348), increasing values for dose metrics predict improved DFS ( P = .043).